La3.65Mg30Sb1.07 as a disordered derivative of Th2Ni17-type structure - Nytka Vitalii; Kordan Vasyl; Pavlyuk Volodymyr (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
La3.65Mg30Sb1.07, hexagonal, P63/mmc (no. 194), a = 10.3895(2) Å, c = 10.2547(3) Å, V = 958.61(5) Å3, Z = 1, R gt(F) = 0.0166, wR ref(F 2) = 0.0429, T = 293(2) K.